A Novel Application of Hydrotropic Solubilization in the Spectrophotometric Analysis of Gatifloxacin in Solid Dosage Form - MAHESHWARI, R.K.; GUPTA, H.M.; SINGH, M.; RAMCHANDANI, U.; PANDEY, S.P. (Asian Journal of Chemistry, 2010)
In the present investigation, hydrotropic solubilization technique has been employed to solubilize the poorly water-soluble fluoroquinolone antibiotic gatifloxacin. There was more than 18-fold enhancement in aqueous solubility of gatifloxa in 1.5 M metformin hydrochloride (MH) and more than 230 times enhancement in 2.0 M sodium benzoate (SB) as compared to aqueous solubility. The selected λmax for spectrophotometric estimation was 333 nm. The hydrotropic agent and the additive used in the manufacture of tablet did not interfere in the analysis. Statistical data proved the accuracy, reproducibility and precision of proposed method.